Synovial fluid and serum concentrations of aminoterminal propeptide of type III procollagen in healthy volunteers and patients with joint disease. - Sharif, M (1996)
OBJECTIVES--To analyse synovial fluid and serum concentrations of the amino-propeptide of the type III procollagen (PIIINP) in normal individuals and patients with joint disease, and to explore the relationship between synovial fluid PIIINP concentrations and the rheumatological diagnosis, local inflammation, and joint disease. METHODS--A radioimmunoassay was used to measure the PIIINP concentrations in serum and knee joint synovial fluid from 16 healthy volunteers and patients with osteoarthritis (OA) (n = 40), rheumatoid arthritis (RA) (n = 30), and psoriatic arthritis (PsA) (n = 12). The PIIINP measurements were related to demographic data, synovial fluid leucocyte counts, and radiographic changes at the knee. RESULTS--Serum PIIINP concentrations were greater in each of the disease groups than in control subjects, but there were no differences between the disease groups. Synovial fluid concentrations of PIIINP were much greater than those in serum, indicating local production, and were significantly greater in RA than in other disease groups (p < 0.001). There was only a weak positive correlation between synovial fluid leucocyte counts, some radiographic changes, and synovial fluid PIIINP concentrations. CONCLUSIONS--These data suggest that synovial fluid PIIINP concentrations may reflect local synovial proliferative processes in joint disease, and that they could be of diagnostic and prognostic value in inflammatory arthropathies.